Theory of Choral Performance - (:unkn) unknown (ХДАК, 2024)
The content of the course reveals the theoretical foundations of choral performance, the issue of interpretation of choral works, the publication contains methodical recommendations for independent performance analysis of choral works. For teachers, masters of specialty 025 "Musical art", educational and professional program "Choir conducting", for students of advanced training and postgraduate education.
program and methodological materials for the course for master’s students of specialty 025 "Musical art", educational and professional program «Сhoral conducting»
Keywords: хорове виконавство; choral performance